Multilevel Participation and Dynamics of Community Project Initiative in Nigeria: A Study of Fourth-Tier Development and Governance in Anambra State, 2016-2021.
This paper explores “Multilevel Participation and Dynamics of Community Project Initiative in Nigeria: A Study in Fourth-Tier Development and Governance, in Anambra State 2016-2021.” Community development, devolution of power and decentralization of decision-making and governance have become crucial worldwide due to the rise in government activities, population growth, and development needs. No doubt in Nigeria, the three tiered system of government has become inadequate due to population and increased government activities. The top-down development model preferred by the government in Nigeria have rather aided disjointed and total absence of development in rural communities. This gives rise for the need to study bottom-up development model that suit the African history of small autonomous nationalities to galvanized development. This paper, therefore, explore the roles(s